ABUNDANCE AND DIVERSITY OF ZOOPLANKTON IN LEMBEH STRAIT, BITUNG, INDONESIA - Rumengan, Inneke F.M.; Akerina, J.; Rampengan, M. M.F.; Masengi, K. W.A. (Marine Research in Indonesia, 2011)
This study examined the diversity and abundance of zooplankton in Lembeh Strait, North Sulawesi. Plankton were sampled monthly from September 2004 to February 2005, collected at four stations using a plankton net of 300 pm meshsize with vertical tow of 10 m water column from the bottom. Environmental factors i.e pH, salinity, current velocity, and dissolved oxygen (DO) were measured in situ at the time of plankton sampling. In general, the environmental conditions of Lembeh Strait were in optimal range for zooplankton. There was a similar pattern in the abundance of zooplankton among stations. Crustacea (mainly Copepoda) was the dominant genera among stations, followed by Ciliata and Tunicata. In all stations, the most abundance taxa (72.3%) was Crustacea (21 genera), mainly copepod (18 genera). There were 7 other classes of holoplankton: Ciliata (2 genera), Rhisopoda (1 genus), Hidrozoa (1 genus), Polychaeta (2 genera), Sagitoedea (1 genus) and Tunicata (2 genera). Meroplankton (larva) were only represented by 5 genera. The most common genera were calanoid copepods, such as Calanus spp., Undinula spp., Eucalanus spp., Rhincalanus spp., Paracalanus spp., and Acartia spp. Diversity, evenness and dominance indices showed that Serena Island, a relatively uncontaminated area, was more productive than the other three stations which were considered as relatively contaminated area with anthrophogenic sources.